Analisis Implementasi Kurikulum Merdeka di SMP Kota Mataram - Iriyani, Sri Astuti; Heri Sopian Hadi; Didin Ardian; Husnul Hafizin (Indo-MathEdu Intellectuals Journal, 2023)
This study was conducted to evaluate curriculum implementation in 12 public junior high schools in Mataram City, focusing on the role of teachers in the dynamics of learning. Using descriptive method and quantitative approach, this study details the features of curriculum implementation, including planning, flow of learning objectives, learning and assessment, use of teaching materials, and Pancasila learning project. The evaluation shows that most parts of the curriculum have been realized, but further adjustments are needed to the guidelines provided by the Ministry of Education and Culture and the Ministry of Research and Technology. Certain areas, such as the use of project modules, require improvement in the utilization of existing resources. Collaboration between teachers, with parents/community/industry, and evaluation/reflection on the curriculum are important aspects of this implementation. However, more structured evaluation is needed to improve the quality and effects of Merdeka Curriculum. Although the implementation stage has gone well, the evaluation highlights that there is room to improve skills and more optimal effects in the learning process. This research provides an overview of the curriculum implementation after one year and identifies areas that require further attention to improve the student learning experience